REVIEW: Possibilities of Mount Lawu to be a National Park (Biodiversitas Journal of Biological Diversity, 2016)
National Park is an area of natural conservation that having indigenous ecosystem managed with zonation system and can be utilized for education, research, crop development and recreation. This concept seems still to be the most suitable technique for biodiversity conservation, and can be applied in Indonesia, where the high biodiversity richness taken place. Mount Lawu and surrounding areas are ideal location to be developed in to National Park. This is due to all criteria needed such as: the width was mare than 10.000 ha, the natural ecosystem and endemic species are still existing, having ancient sites, spiritual and aesthetic value; having typical physiography and physiognomy, as well as the high chance of developing tourism industries. Jobolarangan area is a natural ecosystem that represents the whole ecosystem and problems of Lawu Mountains. This area having quite high diversity and richness consisted of plants, animals and microbes. That development of National Park at Mount Lawu need to be supported by the formation of biodiversity conservation centers, i.e. botanical garden, wild live sanctuary, agro-tourism park, etc., so that becomes an integrated biodiversity conservation area.Â© 2001 Jurusan Biologi FMIPA UNS SurakartaKey words: biodiversity, Jobolarangan, mount Lawu